A Comprehensive Study on Hexa Graph Topology and Its Applications - R.Mohana Priya; S. Santhiya (Utilitas Mathematica, 2025)
The role of this text is to introduce a new graph titled Hexa graph topological space. We define a Hexa graph topological space which has any six subgraphs and six graph decomposition of an undirected graph. Here we provide a new method form to generate topological induced by the edges of the graph and discuss some properties on it. Defining topolo- gies on discrete structures has been a challenging area of research that is relatively obscure. The concept of open sets defined on topology can be extended to the field of graph theory by defining the notion of new open subgraphs on Hexa graph topological spaces.